Peningkatan Prestasi Belajar Siswa Melalui Metode Demonstrasi Dalam Materi Thaharah BAB Wudhu Kelas VII Madrasah Tsanawiyah Ma’arif Klego Mrican Ponorogo Tahun 2023 - samsul hadi Puput dwi; Tamrin Fathoni (Muaddib: Jurnal Pendidikan Agama Islam, 2024)
This research aims to determine whether the demonstration method can improve student learning achievement using ablution material for class VII students at MTs Ma'arif Klego Mrican Ponorogo. This classroom action research uses a demonstration method by demonstrating or demonstrating to students a process, situation that is being studied so that the process of students' acceptance of the lesson will be more impressive in depth. This research is a PTK with 3 cycles through 4 stages, namely planning, implementation, observation and reflection. The subjects of this research were 32 students. The hypothesis proposed is that if the demonstration method can be used well, it can improve student learning achievement in Fiqh subjects in class VII students at MTs Ma'arif Klego Mrican Ponorogo. The success indicator is 75% with a KKM of 75. Data collection techniques are observation. Data analysis techniques with formulas to determine average values ​​and percentages. The results showed that learning achievement in cycle I was 44% or 14 students with a KKM of 75, cycle II was 56% or 18 students with a KKM of 75 and in cycle III was 81% or 26 students for the pillars of ablution and was 87.5%. or 28 students for the sunnah ablution material with a KKM of 75. The increase in student learning achievement in cycle I to cycle II was 12% with a KKM 75, the increase in achievement in cycle II to cycle III with the pillars of ablution material was 25% and in the sunnah ablution material was 31 .5%.